An Investigation of the Knowledge and Perceptions of Arthritis amongst the Student Population in Ireland. - Laura Dunleavy; Máire McCallion (SURE Journal: (Science Undergraduate Research Experience Journal))
Background: Arthritis is a term used to categorise many diseases that primarily affect joints. It is a highly prevalent disease worldwide with approximately 915,000 individuals living with it in Ireland. Support is vital and it is important that individuals in college have a good understanding of disabilities. Previous studies found that there is a lack of knowledge and awareness about rheumatic diseases amongst the general public, however, no studies focused on the student population. Aim: To investigate students’ knowledge and perception of arthritis and to determine whether education and more awareness about arthritis is needed amongst students. Methods: This was a cross-sectional study which was primarily quantitative. The measurement tool used was a web-based questionnaire which was distributed via social media platforms such as Facebook and Instagram and emails that were sent to health science students in IT Sligo. The questions focused on knowledge and perceptions of arthritis and suggestions about how students felt they could be educated on the topic. Both Microsoft Excel 2008 and the IBM SPSS Statistics version 26 software were used for analysation of data. Results: A total of 190 participants took part in the study and 186 participants (55 male, 129 female and 2 unspecified) met the inclusion criteria. The mean age of participants was 20.4±2.01 years. The knowledge of arthritis was suboptimal. The percentage of respondents who obtained the correct answers in relation to questions on how many different types of arthritis there are and how many people they think are affected by arthritis in Ireland were 19.4% and 43.0%, respectively. More males were associated with knowing the number of different types of arthritis (Males=30.9%, Females= 14.7%, p Females were associated with having more knowledge and awareness in relation to the need for medication to control arthritis (Females=97.7%, Males=85.5%, p how many people they think are affected by arthritis (Females=50.4%, Males=27.3%, p and the different types of supports that are necessary for students with arthritis. There was a lack of awareness about the different body parts that can be affected by arthritis. Overall, participants had a good knowledge in relation to the control of arthritis. Conclusion: This study found that there was a lack of knowledge and awareness about arthritis amongst the student population. Females had a better knowledge on many aspects of arthritis in comparison to males. Moreover, participants indicated that they would like to learn more about the disease. Intervention studies are needed to ascertain how best to increase knowledge of arthritis amongst students.